New Formula on the Conjugate Gradient Method for Unconstrained Optimization and its Application - Sulaiman, Ranen M.; Abdullah, Zeyad M.; Hassan, Basim A. (Iraqi Journal of Science, 2024)
In this paper, we have presented a new formula by applying the conjugacy condition for the second-order Taylor expansion. In comparison with classic conjugate gradient methods, the new formula uses both available gradient and function value information. The formula’s global convergence findings are described. Numerical results demonstrate that this strategy is effective and its application.